The intermediary as an institutional entrepreneur: Institutional change and stability in triple-helix cooperation - Florian Poppen; Reinhold Decker (Triple Helix, 2018)
This paper aims to illustrate how the triple-helix concept can be implemented on a city level by establishing an intermediary among the scientific, economic, and public administration spheres and civil society. By using the example of Bielefeld 2000plus, an initiative founded for this particular purpose, this paper shows that in today's knowledge society, certain inter-organizational conflicts and challenges regarding cooperation may arise that an intermediary actor can channel efficiently. Furthermore, Bielefeld 2000plus serves as a prototypical example and is used to derive a theoretical model of such an intermediary actor as both the product of and platform for institutional entrepreneurs who try to elicit institutional change. Drawing on extant literature that examines intermediaries with the triple-helix concept, as well as institutional entrepreneurs, this paper discusses how an intermediary can act as an institutional entrepreneur by adopting a bifunctional framework, with all the advantages and disadvantages that this entails. This framework is condensed into the Bifunctional Intermediary (BFI) Model, which may benefit researchers studying triple-helix processes and practitioners seeking to establish an intermediary.
Keywords: 330; Intermediary; Triple helix; Urban development; Cooperation; Knowledge society